Creative thinking skills of prospective physics teacher. (April 2020) - Rizal, R; Rusdiana, D; Setiawan, W; Siahaan, P
Abstract: The 21 st century demands high quality human resources that can compete in global competition. The good quality human resources come from the good quality education process which train learner with skills to solve problems, to find alternative solutions in problem solving, and to think reflectively. These skills are included in creative thinking skills which is important to be developed for prospective physics teacher. This study aimed to identify the creative thinking skills of prospective physics teacher who have attended lectures of general physics, basic physics, and physics for school. By using the creative thinking skills test and interview, the researcher tried to explore four aspects of creative thinking consisting of fluency, flexibility, originality, and elaboration. The results of this study indicated the creative thinking skills of prospective physics teacher were in the low category with mean was 43.75 from a maximum scale of 100. The details of the means of each aspect of creative thinking skills were expressed as follows fluency (57), flexibility (43), originality (34), and elaboration (41). The low level of creative thinking skills of prospective physics teachers is thought to be due to lecture activities that do not provide an opportunity to practice creative thinking skills.